Hubungan Hukum Antara Rentenir Dan Debitur Sebagai Peminjam Menurut Kitab Undang-Undang Hukum Perdata - Siti Fatima Iha; Merry Tjoanda; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The law of treaties in Indonesia is open, namely the granting of the widest possible freedom to anyone to make agreements with the content and nature as desired, as long as they do not violate the law, public order, and morality.Purposes of the Research: The purpose of this study is to be able to find out and explain how the form of the legal relationship between debtors as borrowers and moneylenders in the Civil Code, and to be able to find out and explain how the form of problem solving if the debtor breaks his promise. Methods of the Research: The method used in this study is a normative juridical method with a statutory approach, and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The legal material is analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the results of the study, it shows that the first problem is the legal relationship between debtors as borrowers and moneylenders is a legal relationship between borrowing and borrowing money, this legal relationship is included in a two-sided legal relationship, namely a legal relationship between two parties accompanied by rights and obligations on each party, both parties each party has the authority/right to request something from the other party, on the other hand, each party is also obliged to give something to the other party. The second problem solving the problem if the debtor breaks his promise is by going through the courts, the loan shark can give a summons to the debtor first or through consensus deliberation by negotiating or negotiating between the two parties, the debtor can request an extension of the time for paying debts to the moneylender.